ANALISIS PREFERENSI SISWA MELANJUTKAN STUDI KE SMP ISLAMIC BOARDING SCHOOL BABUSALAM PEKANBARU TP. 2014/2015 - Titin Asmida Titin Asmida; Zulfan Saam Zulfan Saam; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to: (a) Analyzeaspects ofthe internalfactorsthatbecomethe preferenceof studentschoosing islamic, (b) AnalyzeaspectsExternalfactorsthatbecomethe preferenceof studentschoosing islamic Boarding School, (c) Analyzingthe category ofinternal factorsthatbecomethe preferenceof studentschoosing islamic Boarding School, (d) Analyzingthe category ofexternal factorsintothe preferencesof studentschoosing islamic Boarding School. The method usedinthisstudyis adescriptivestudy, Samplingtechniquein this study50% of the totalpopulationusing thetechniqueRandomsamplin . Theresults ofthis study are: (a) aspects ofthe internalfactorsthatbecamepreferencestudentschoose islamic Boarding Schoolisbecauseyou want toexplorethe religion of Islam. (b) External factorsthatbecomePreferencesstudentschooseislocatedonthe indicatoratthe boarding schoolatmospheremore fun, (c) Categoryinternalfactorsbecomethe preferenceof studentschoosing islamic Boarding Schoolin middle category, (d) Categoryexternal factorsbecomepreferencestudentschoose islamic Boarding Schoolin middle category. Keywords: Preferences, SMP, Boarding School